Digital innovations for adolescent mental health: evaluating the impact of genziheal web-based education model - Wiguna, Reza Indra; Ardhana, Valian Yoga Pudya; Safitri, Rias Pratiwi; Lita, Baiq Fitria Frisma; Pa’ni, D Mustamu Qamal; Apriani, Lia Arian (Universitas Airlangga, 2025)
Introduction: Mental health problems among adolescents remain a global public health concern, highlighting the need for accessible and innovative educational interventions. This study evaluated the effectiveness of a web-based mental health education model through the Genziheal platform in improving knowledge levels and reducing symptoms of mental health disorders among adolescent students. Methods: A quasi-experimental, pretest-posttest control group design was employed involving 130 senior high school students (intervention group: n=80; control group: n=50). Data were collected using the Self-Reporting Questionnaire-29 (SRQ-29) and a validated mental health knowledge questionnaire. Paired t-test and Mann-Whitney tests were used for analysis. Results: The intervention group demonstrated a significant increase in mental health knowledge (mean score improved from 11.0 ± 2.8 to 12.2 ± 3.2; p = 0.008), while no significant change was observed in the control group. However, no significant differences were found in mental health symptoms between pre- and post-test stages in both groups (p > 0.05). Conclusions: The Genziheal platform effectively enhanced students’ mental health literacy but did not significantly reduce symptoms of mental health disorders. These findings suggest that web-based educational tools can support mental health awareness among adolescents but should be complemented with parental involvement and professional support to address psychological symptoms. This study also highlights the potential integration of digital mental health interventions into school-based health promotion programs. The findings contribute to the development of scalable, culturally contextualized digital health promotion tools, particularly in resource-constrained settings such as Indonesia.